2019
DOI: 10.1108/pijpsm-12-2018-0184
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of using real-time, objective measurements of physiological stress among law enforcement officers in Dallas, Texas

Abstract: Purpose Law enforcement officers (LEOs) suffer from premature mortality, intentional and unintentional injury, suicide and are at an increased risk for several non-communicable disease outcomes including cardiovascular disease and several cancers, compared to those employed in other occupations. Repeated exposure to stressful and traumatic stimuli is a possible mechanism driving these adverse health outcomes among LEOs. To better identify the sources of these health problems, the purpose of this paper is to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Other studies have tracked mood and provided financial incentives to engage in remote monitoring (Losina et al, 2017; Mark et al, 2016; Padmaja et al, 2019). These studies, as well as others, have shown that smartwatch accuracy in tracking is sufficient for baseline screening (Benedetto et al, 2018; Feehan et al, 2018; Reingle Gonzalez et al, 2019). Heart rate is a suitable variable to capture on the smartwatch, and heart rate can be used as a proxy for times of increased stress (Nakayama et al, 2018; Padmaja et al, 2019).…”
Section: Discussionmentioning
confidence: 75%
“…Other studies have tracked mood and provided financial incentives to engage in remote monitoring (Losina et al, 2017; Mark et al, 2016; Padmaja et al, 2019). These studies, as well as others, have shown that smartwatch accuracy in tracking is sufficient for baseline screening (Benedetto et al, 2018; Feehan et al, 2018; Reingle Gonzalez et al, 2019). Heart rate is a suitable variable to capture on the smartwatch, and heart rate can be used as a proxy for times of increased stress (Nakayama et al, 2018; Padmaja et al, 2019).…”
Section: Discussionmentioning
confidence: 75%
“…The performance of each participant was captured on video, and later, the expert reviewed the footage to validate the results. In terms of the procedures for carrying the rearm (Table 2), the measurement was conducted in a similar manner: either present (0) or absent (10) was recorded. However, in this case, 10 points were allocated to each missing procedure.…”
Section: Methodsmentioning
confidence: 99%
“…She was also the principal investigator of two funded projects that included a substantial amount of qualitative data. These projects have resulted in seven peer-reviewed publications [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ] and one report that includes exclusively qualitative data [ 15 ]. The principal investigator has also co-authored a research methods textbook that includes a chapter solely focused on qualitative and mixed-methods data collection methodologies [ 16 ].…”
Section: Methodsmentioning
confidence: 99%